PENGARUH DIMENSI KUALITAS JASA DAN KEPUASAN KONSUMEN TERHADAP REKOMENDASI DARI MULUT KE MULUT PADA TAMAN WISATA BAHARI PASIR PUTIH SITUBONDO - Hendra Syahputra (UNEJ e-Proceeding)
This research was conducted in order to determine the effect of service quality established by the dimensions of the service quality to customer satisfaction or visitors, and word of mouth recommendations. Subjects were visitors Taman Wisata Bahari Pasir Putih Situbondo, with a sample of 150 people. The sampling method Sampling Asidental. Data analyzed by using SEM (Structural Equation Modelling) by Amos 20. The results of the study showed that the effect of the eight dimensions (performace, features, reliability, Comformance to specification, durability, serviceability, aesthetics, perceived quality) segnifikan affect service quality to satisfaction consumers and recommendation by word of mouth, except aesthetics not significant effect on recommendation by word of mouth because of testing using SEM value is the lowest, so the hypothesis fourteen rejected, is considered the uniqueness of Taman Wisata Bahari Pasir Putih Situbondo decreased interest because there is no change fasilatas every year.